PENGARUH OPTIMALISASI SELF-REGULATED LEARNING TERHADAP KINERJA AKADEMIK MAHASISWA DALAM PEMBELAJARAN DARING - Fathan, Naufal; Winarno, Winarno; Azizah, Fahriza Nurul; Kurnia, Iin (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to analyze the effect of optimizing self-regulated learning (SRL) on students’ academic performance in online learning. The development of online learning systems following the COVID-19 pandemic has posed new challenges for students, such as low learning motivation, limited engagement, and difficulties in time management. Optimizing SRL is considered a key strategy to overcome these issues. This research uses a quantitative approach with a correlational survey design. Data were obtained from a standardized and validated SRL questionnaire, along with students' Grade Point Average (GPA) as an indicator of academic performance. The data were analyzed using Pearson correlation with the assistance of SPSS Statistics 23. The results show a significant positive relationship between optimized SRL and students’ academic performance. The higher the students’ SRL level, the better their academic performance in online learning. These findings highlight that optimizing SRL can be a crucial strategy to enhance students' academic success in online learning environments at the university level. Keyword: Self-regulated learning, online learning, academic performance, university students, Pearson correlation. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh optimalisasi self-regulated learning (SRL) terhadap kinerja akademik mahasiswa dalam pembelajaran daring. Perkembangan sistem pembelajaran daring setelah pandemi COVID-19 menghadirkan tantangan baru bagi mahasiswa, seperti rendahnya motivasi belajar, keterlibatan yang minim, serta kesulitan dalam pengelolaan waktu. Optimalisasi SRL dipandang sebagai salah satu strategi untuk mengatasi permasalahan tersebut. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei korelasional. Data diperoleh melalui kuesioner SRL yang telah terstandarisasi dan tervalidasi, serta data Indeks Prestasi Semester (IPS) mahasiswa sebagai indikator kinerja akademik. Analisis dilakukan menggunakan uji korelasi Pearson dengan bantuan perangkat lunak SPSS Statistics 23. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara tingkat optimalisasi SRL dan kinerja akademik mahasiswa. Semakin tinggi tingkat SRL mahasiswa, semakin baik pula kinerja akademiknya dalam pembelajaran daring. Temuan ini menegaskan bahwa optimalisasi SRL dapat menjadi strategi penting untuk meningkatkan keberhasilan akademik mahasiswa dalam konteks pembelajaran daring di perguruan tinggi. Kata kunci: Self-regulated learning, pembelajaran daring, kinerja akademik, mahasiswa, korelasi Pearson.